Letter to Jane Tolmach from Richard Nevins - Richard Nevins:::::: (1968)
A brief thank-you letter from Richard Nevins, Chairman of the California State Board of Equalization, to Jane Tolmach of the Democratic State Central Committee of California. In the letter, Nevins expresses appreciation for a photograph taken at the Jefferson-Jackson Day dinner featuring himself and Mayor Stokes, noting that he finds the picture "most attractive." He closes the letter sincerely and includes his title.